Barreras de acceso en salud para la atención materno perinatal en las comunidades indígenas de Latinoamérica: revisión narrativa de la literatura (2021)
The objective of this study is to describe the barriers to health access for maternal perinatal care in indigenous communities in Latin America through a literature review. In the materials and methods, a literary narrative review of the indigenous communities of Latin America was carried out, based on the PRISMA guide, a qualitative reading and analysis of the information is carried out, where the inclusion criteria were based on the articles having a range of 2009 to 2019, which would address the issue that included Latin American communities, were Full text and the databases used for this research were Scielo, Elsevier, Science Direct, Journals, Pubmed, Scopus, Web Of Science, Cochrane, Biblioteca Virtual de Public health, Lilacs and Cuiden.